Chirality of male genitalia in Otomantis casaica Giglio-Tos, 1915 (Mantodea: Hymenopodidae, Acromantinae) - Lombardo, Francesco; Stiewe, Martin B. D.; Ippolito, Salvatrice (Zootaxa, 2016)
Reversal of male genitalia are known in various insect orders, such as in Odonata, Orthoptera, Dermaptera, Hemiptera and Trichoptera (Schilthuizen 2007) and, within the Dictyoptera, in several species of Ectobiinae (Blattodea) (Bohn 1987), and Mantodea. Balderson (1978) first described reversal of the phallic complex in Stenomantis Saussure and Ciulfina Giglio-Tos, reporting this condition in eleven of 17 specimens representing two species of the latter—informally named as “Ciulfina sp.2” and “Ciulfina sp.7” (see Balderson 1978: 238). Subsequently, Anisyutkin & Gorochov (2004) reported the same condition at the time of describing Haania doroshenkoi from Cambodia. The male external genitalia within the Mantodea (“praying mantises”) are markedly asymmetrical and generally develop in a single orientation (Klass 1997; Huber et al. 2007). Typically, the phallic complex consists of three phallic lobes surrounding the gonopore, all contained in a genital chamber between the ninth sternite and the paraprocts. Two of the three phallic lobes (phallomeres of La Greca 1955) are situated above the gonopore—one to the left and one to the right—while the third lies ventral to the genital opening. The right phallomere (RP) (Fig.1) (“right epiphallus” of Beier 1964) is usually dorsally positioned and its base extends almost completely across the wall of the genital chamber. The left phallomere (LP) (Fig.1) (“left epiphallus” of Beier 1964) is the most complex of the three lobes and it lies above the ventral phallomere (VP) (Fig.1) (hypophallus of Beier 1964).